Variable frequency microwave induced CO2 Boudouard reaction over biochar - Jurong Ren; Jianchun Jiang; Jia Wang; Xiangzhou Yuan; Ao Wang (Biochar, 2024)
Abstract The Boudouard reaction presents promising application prospects as a straightforward and efficient method for CO2 conversion. However, its advancement is hindered primarily by elevated activation energy and a diminished conversion rate. This study employed a microwave reactor with a variable frequency as the initial approach to catalyze the CO2 Boudouard reaction over biochar, with the primary objective of producing renewable CO. The study systematically investigated the influence of various variables, including the heating source, microwave frequency, microwave power, gas hourly space velocity (GHSV), and carrier gas, on the conversion of CO2 and the selectivity towards CO. The experimental findings indicate that under static conditions, with a fixed microwave frequency set at 2450 MHz and 100 W microwave power, the Boudouard reaction did not initiate. Conversely, a CO2 conversion rate of 8.8% was achieved when utilizing a microwave frequency of 4225 MHz. Under this unique frequency, further elevating the microwave power to 275 W leads to the complete conversion of CO2. Furthermore, a comparative analysis between microwave and electrical heating revealed that the CO production rate was 37.7  μmol kJ−1 for microwave heating, in stark contrast to the considerably lower rate of 0.2  μmol kJ−1 observed for electric heating. Following the reaction, the biochar retained its robust 3D skeleton structure and abundant pore configuration. Notably, the dielectric constant increased by a factor of 1.8 compared to its initial state, rendering it a promising microwave-absorbing material. Graphical Abstract